Estudo das curvas de retenção e condutividade hidráulica estimadas pela equação de van Genuchten (1980) para diferentes tipos de solo - Gonçalves, Fernanda Vescovi (2012)
The van Genuchten (1980) equation has been widely used in the literature to represent analytically the soil water retention curve, and there are several published database tables which allow estimate the van Genuchten (1980) parameters (VG parameters) for different soils and regions. The equation enables one to derive closed-form analytical expressions for the unsaturated hydraulic conductivity function using Burdine (1953) and Mualem (1976) models. The objective of this dissertation is to study published database tables of the retention and hydraulic conductivity functions for different soils (Wosten et al.; 1999; Schaap et al., 2001; Hodnett and Tomasella, 2002; and Gerscovich and Sayão, 2002), and quantify the variation of VG parameters with the grain size distribution of these soils. The different experimental methods, the large variability of soils, and the lack of complete information of the soil properties of the investigated data, and the lack of physical meaning of VGparameters did not allow to define functions to quantify the variation of VGparameters with the grain size distribution for the investigated soils. The results suggest that there is no dependency between the VG parameters and the fine content of the investigated silty sand soils when the percentage of fines is such that it fills all large grains voids. In this case, the limited classification based only on soil texture can not be used to estimate the VG parameters. The variation of saturated hydraulic conductivity with fines content provides a useful means of assessing the existence of the dependency between the VG parameters and the soil texture. For the silty sandy soils evaluated in this study, when the fines content is higher that 30% there is no dependency between the VG parameters and the fines content. It is also observed that the soils that do not exhibit a significant difference in their saturated hydraulic conductivity values may exhibit large variations in their unsaturated hydraulic conductivity values depending on their fines content. For high suction values, the relative permeability of the soil specimens with 10% of fines content can be up to 1016 times lower than that of the soil specimens with 90% of fines content.